Modulation of Co spin state at Co3O4 crystalline-amorphous interfaces for CO oxidation and N2O decomposition - Yunpeng Long; Xiao Zhu; Chuan Gao; Wenzhe Si; Junhua Li; Yue Peng (Nature Communications)
Abstract Modulation of electronic spin states in cobalt-based catalysts is an effective strategy for molecule activations. Crystalline-amorphous interfaces often exhibit unique catalytic properties due to disruptions of long-range order and alterations in electronic structure. However, the mechanisms of molecule activation and spin states at interfaces remain elusive. Herein, we present a Co3O4 spinel-based catalyst featuring crystalline-amorphous interfaces. Characterization analyses confirm that tetrahedral Co2+ is selectively etched from bulk spinel, forming amorphous CoO islands on the surface. The resultant symmetry breaking in the coordination field induces a reconstruction of the Co3+ 3  d orbitals, leading to high-spin states. In CO oxidation, the interface serves as novel active sites with a lower energy barrier, facilitated by lattice oxygen activation. In N2O decomposition, the interface promotes reassociation of dissociated oxygen through quantum spin exchange interactions. This work provides a straightforward approach to modulating the spin state of interfaces and elucidates their role in molecule activations.